Tracheostomal Myiasis: A Case Report and Review of the Literature - S. Prasanna Kumar; A. Ravikumar; L. Somu; P. Vijaya Prabhu; Rajavel Mundakannan Subbaiya Periyasamy Subbaraj (Case Reports in Otolaryngology)
“Myiasis” is considered in Hindu mythology as “God's punishment for sinners.” It is known to infest live human or animal tissue. Literature abounds with reports of myiasis affecting the nasal cavity, ear, nonhealing ulcers, exophytic malignant growth, and cutaneous tissue. But report of myiasis of the tracheal stoma is rare. Only a few cases of tracheal myiasis have been reported in literature. We report a case of tracheostomal myiasis in an elderly male. The species which had infested the stoma was identified as Chrysomya bezziana, an obligate parasite. This is to our knowledge the first case report of an obligate parasite (Chrysomya bezziana) infestation of the tracheostoma from India.